A decision model for investment analysis in CNC centers and CAM technology. (May 2019) - Plaza, Malgorzata; Zebala, Wojciech
Highlights: Companies must invest in CNC centers and CAM systems in order to machine challenging applications. NC programmers need to learn advanced technology which support planning of machining strategies. NC programmer's skills and learning abilities have ramifications for product quality and cost. NC programmer's learning curve has high impact on the value generated by CNC/CAM technology. Decision Model allows to analyze the impact of programmer's learning curve on CNC/CAM investment. Abstract: An aircraft engine housing is a complex thin-walled structure composed of hard to machine Inconel. Machining of complex geometries requires a multi-axis machining center. The programmers who plan the machining strategy need a sophisticated technology, since both processes are very expensive. The demand for challenging applications is rapidly growing. The machining industry must invest in machines and technology in order to stay competitive. This study offers an effective decision tool that supports such complex examination. We use this tool to determine the conditions under which the investment in technology is beneficial. We argue that the skills, experience and learning abilities of programmers have serious ramifications for: the duration of strategy planning, the quality of the final product and the efficiency of the machining process. We demonstrate that the programmers' performance curve has high impact on the value generated by technology and must be considered on equally important footing with the material, machine, tooling and labor costs when technology investment is examined.